Changes in Foxp3-Positive Regulatory T Cell Number in the Intestine of Dogs With Idiopathic Inflammatory Bowel Disease and Intestinal Lymphoma. (January 2016) - Maeda, S.; Ohno, K.; Fujiwara-Igarashi, A.; Uchida, K.; Tsujimoto, H.
Although regulatory T cells (Tregs) play an integral role in immunologic tolerance and the maintenance of intestinal homeostasis, their involvement in canine gastrointestinal diseases, including idiopathic inflammatory bowel disease (IBD) and intestinal lymphoma, remains unclear. Here we show altered numbers of forkhead box P3 (Foxp3)–positive Tregs in the intestine of dogs with IBD and intestinal lymphoma. IBD was diagnosed in 48 dogs; small cell intestinal lymphoma was diagnosed in 46 dogs; large cell intestinal lymphoma was diagnosed in 30 dogs; and 25 healthy beagles were used as normal controls. Foxp3-positive Tregs in the duodenal mucosa were examined by immunohistochemistry and immunofluorescence. Duodenal expression of interleukin-10 mRNA was quantified by real-time reverse transcription polymerase chain reaction. The number of Foxp3-positive lamina propria cells and the expression of interleukin-10 mRNA were significantly lower in dogs with IBD than in healthy dogs and dogs with intestinal lymphoma. The number of Foxp3-positive intraepithelial cells was higher in dogs with small cell intestinal lymphoma. Some large cell intestinal lymphoma cases had high numbers of Foxp3-positive cells, but the increase was not statistically significant. Double-labeling immunofluorescence showed that CD3-positive granzyme B–negative helper T cells expressed Foxp3. In small cell intestinal lymphoma cases, the overall survival of dogs with a high Treg density was significantly worse than that of dogs with a normal Treg density. These results suggest that a change in the number of Foxp3-positive Tregs contributes to the pathogenesis of canine IBD and intestinal lymphoma by disrupting mucosal tolerance and suppressing antitumor immunity, respectively.